Development of Comic-Based Learning Media on the Use of Capital Letters for Grade II Students at State Elementary School - Hidayat, Ryan; Mufidah, Luluk Indarinul (PGMI, STAI Miftahul Ula Nganjuk, 2024)
The development of comic-based learning media on the use of capital letters for Grade II students at State Elementary School 2 Lengkonglor was based on several identified problems, namely the learning objectives—especially regarding the use of capital letters—had not been fully achieved, and the lack of available learning media due to inadequate facilities. In addition, both students and teachers still require learning media that are practical and engaging. The objectives of this study were: (1) to develop comic-based learning media on the use of capital letters for Grade II students at State Elementary School 2 Lengkonglor; (2) to describe the validity of the developed comic-based learning media on the use of capital letters; and (3) to describe the level of practicality and attractiveness of the comic-based learning media in teaching the use of capital letters for Grade II students at State Elementary School 2 Lengkonglor. This research employed a Research and Development (R&D) method using the ADDIE model. The subjects of this study were 17 Grade II students of State Elementary School 2 Lengkonglor. Data collection methods included observation, interviews, and questionnaires. The results of the study generally showed that the media expert validation test obtained a percentage of 98%, the material expert validation test obtained 99.2%, and the language expert validation test obtained 100%. The practicality and attractiveness tests conducted with the Grade II teacher of State Elementary School 2 Lengkonglor obtained a percentage of 100%. Furthermore, the practicality and attractiveness tests conducted on Grade II students in both small-scale and large-scale trials also obtained a percentage of 100%. Therefore, the comic-based learning media on the use of capital letters is considered highly feasible for use as a learning medium.